Evaluasi ketersediaan obat di beberapa puskesmas wilayah kabupaten X tahun 2019 - Andini Rezeki; Bella Na Fhory; Muhamad Saif Roies Yasa; Syahriah Syahriah; Nashrul Wathan (Sasambo Journal of Pharmacy, 2021)
Drug management in public health centers (Puskesmas) needs to be solve properly to ensure continuing availability and affordability medical services that efficient, effective and rational. The aims of this study are to describe and evaluate drug management in four Puskesmas on Kabupaten X, especially in planning, demanding, receiving, distribution, and storage. This study is a descriptive-evaluative study, with quantitative and qualitative methods, using retrospective data in 2019. The results show that suitability of the types of drugs available with the district drug formulary : 93.46-98.57%; accuracy of drug demand 114-416%; receiving accuracy 76-128%; dead stock  1.3-31.57%; prescriptioning generic drugs 94.72-100%; and the value of damaged drugs 0-17,37%. Results of this study can be concluded that the drug management in four Puskesmas still not optimal because not in accordance with the standard.